The production of extracellular protease using bacillus subtilis : effect of temperature and agitation speed - Mohd Fadli, Abdullah (2006)
Production of extracellular protease refers to proteases produced from microorganisms and functions out of the cell in which it was originated. In this term, the microorganism was sought to be normal mesophilic bacteria. The experiment was conducted to evaluate the effects of temperature and agitation speed of the incubator shaker towards the production of extracellular protease. Optimization of the enzyme production condition involving the two parameters was also made using statistical software. Typical methods conducted in previous researches were utilized in the experiments using different temperature and agitation speed. However, in previous researches, experiments were conducted through one-factor-at-a-time method (OF AT) but in this experiment, that method was overrun and designed beforehand using Minitab. The standard procedures of protease assay were carried out when experimenting. The bacteria were re-cultured to enable its functionality to serve its purpose. The results obtained proved that both parameters had significant effects if stood alone towards the production, however had to interact with each other due to randomization of the values implemented in the experiments. Simple analysis was not an option therefore the results were opted to be analyzed by Minitab and also the condition of protease production was optimized.